Inverse Synthetic Aperture Secondary Radar Concept for Precise Wireless Positioning - Vossiek, Martin; Urban, Alexander; Max, Stephan; Gulden, Peter (IEEE Transactions on Microwave Theory and Techniques, 2007)
In this paper, the novel inverse synthetic aperture secondary radar wireless positioning technique is introduced. The proposed concept allows for a precise spatial localization of a backscatter transponder even in dense multipath environments. A novel secondary radar signal evaluation concept compensates for the unknown modulation phase of the returned signal and thus leads to radar signals comparable to common primary radar. With use of this concept, inverse synthetic aperture radar algorithms can be applied to the signals of backscatter transponder systems. In simulations and first experiments, we used a broadband holographic reconstruction principle to realize the inverse synthetic aperture approach. The movement of the transponder along a short arbitrary aperture path is determined with assisting relative sensors (dead reckoning or inertia sensors). A set of signals measured along the aperture is adaptively focused to the transponder position. By this focusing technique, multipath reflections can be suppressed impressively and a precise indoor positioning becomes feasible. With our technique, completely new and powerful options for integrated navigation and sensor fusion in RF identification systems and wireless local positioning systems are now possible. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.invers
Keywords: Position measurement; Radio navigation; Secondary radar; Synthetic aperture radar (SAR); Transponders